Cystatin M/E Variant Causes Autosomal Dominant Keratosis Follicularis Spinulosa Decalvans by Dysregulating Cathepsins L and V - Eckl, Katja M.; Gruber, Robert; Brennan, Louise; Marriott, Andrew; Plank, Roswitha; Moosbrugger-Martinz, Verena; Blunder, Stefan; Schossig, Anna; Altmüller, Janine; Thiele, Holger; Nürnberg, Peter; Zschocke, Johannes; et al. (Frontiers in Genetics, 2021)
Keratosis follicularis spinulosa decalvans (KFSD) is a rare cornification disorder with an X-linked recessive inheritance in most cases. Pathogenic variants causing X-linked KFSD have been described in MBTPS2, the gene for a membrane-bound zinc metalloprotease that is involved in the cleavage of sterol regulatory element binding proteins important for the control of transcription. Few families have been identified with an autosomal dominant inheritance of KFSD. We present two members of an Austrian family with a phenotype of KFSD, a mother and her son. The disease was not observed in her parents, pointing to a dominant inheritance with a de novo mutation in the index patient. Using whole-exome sequencing, we identified a heterozygous missense variant in CST6 in DNA samples from the index patient and her affected son. In line with family history, the variant was not present in samples from her parents. CST6 codes for cystatin M/E, a cysteine protease inhibitor. Patient keratinocytes showed increased expression of cathepsin genes CTSL and CTSV and reduced expression of transglutaminase genes TGM1 and TGM3. A relative gain of active, cleaved transglutaminases was found in patient keratinocytes compared to control cells. The variant found in CST6 is expected to affect protein targeting and results in marked disruption of the balance between cystatin M/E activity and its target proteases and eventually transglutaminases 1 and 3. This disturbance leads to an impairment of terminal epidermal differentiation and proper hair shaft formation seen in KFSD.